2017
DOI: 10.1111/1475-6765.12189
|View full text |Cite
|
Sign up to set email alerts
|

Getting away with foul play? The importance of formal and informal oversight institutions for electoral integrity

Abstract: Abstract. Electoral integrity is increasingly being recognised as an important component of democracy, yet scholars still have limited understanding of the circumstances under which elections are most likely to be free, fair and genuine. This article posits that effective oversight institutions play a key role in scrutinising the electoral process and holding those with an interest in the electoral outcome to account. The main insight is that deficiencies in formal electoral management can be effectively compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 60 publications
0
48
1
2
Order By: Relevance
“…Variables related to local socio-economic development (Lehoucq 2003;Lehoucq and Molina Jiménez 2002;Stokes 2007); the degree of fiscal dependence of a locality on the national purse (Gervasoni 2010); regional machine politics (Eisenstadt 2004;Gibson 2013); or media freedom (Birch and Ham 2014), could all affect the probability of manipulations in individual regions, or the likelihood that electoral results are marred with fraud rather than being products of voter choice or strategic voting. In our analysis, it is therefore important to perform fully parametric tests, such as multivariate regressions, that would control for these region-specific variations; non-parametric and univariate analyses of sub-national fraud heterogeneity are most likely affected by omitted variable bias and may generate spurious results.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables related to local socio-economic development (Lehoucq 2003;Lehoucq and Molina Jiménez 2002;Stokes 2007); the degree of fiscal dependence of a locality on the national purse (Gervasoni 2010); regional machine politics (Eisenstadt 2004;Gibson 2013); or media freedom (Birch and Ham 2014), could all affect the probability of manipulations in individual regions, or the likelihood that electoral results are marred with fraud rather than being products of voter choice or strategic voting. In our analysis, it is therefore important to perform fully parametric tests, such as multivariate regressions, that would control for these region-specific variations; non-parametric and univariate analyses of sub-national fraud heterogeneity are most likely affected by omitted variable bias and may generate spurious results.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Urbanisation, which tends to co-vary with our Fiscal Transfers and with University degree variables; and Media freedom, a variable employed in other studies of electoral malpractice (Birch and Ham 2014;Wilkinson 2007) and which we capture by employing an index developed by scholars at the Moscow Carnegie Centre, a respected think tank (Petrov and Titkov 2013). The index encompasses regional media pluralism, censorship, and independence of media sources from municipal and regional authorities.…”
Section: Russians In Regional Populations; and Regional Status (Oblasmentioning
confidence: 99%
“…Finally, our findings indicate that sub-national post-electoral protest could be regarded as an additional mechanism for uncovering spatial variations in fraud, complementary to the "forensic" techniques discussed in this paper. Protests could also complement the formal mechanisms of electoral scrutiny such as election monitoring and observation, which, as a number of recent studies have noted, can be effective both at exposing fraud and preventing it (Birch and Ham 2014;Hyde and Marinov 2014;Hyde 2007) (but see (Simpser and Donno 2012)). Although beyond the scope of this study, relatedly, we may also conjecture that protest may serve as an additional signalling mechanism in cases where rulers seek to "displace" (Ichino and Schuendeln 2012) fraud from one locality to another as a way of avoiding electoral scrutiny by monitors who are often spread thinly across the territory of a particular country and do not usually cover each and every electoral precinct.…”
Section: Resultsmentioning
confidence: 99%
“…(For a discussion, see SI). This would explain why some other studies have found media freedom to have a significant moderating effect on fraud (Birch and Ham 2014). This variable also captures general levels of regional political openness, so…”
Section: Oblast and Russians Russia's Ethnically-defined Republics Hmentioning
confidence: 94%
“…In this regard, the impartiality of the EMB is what determines the credibility of holding competitive elections. A number of studies, however, have demonstrated that the formal independence of electoral management bodies is far less important than their de facto autonomy (Birch, 2011;Birch & Van Ham, 2017;Hartlyn, McCoy & Mustillo, 2008;Opitz, Fjelde & Höglund, 2013). De facto autonomy is a matter of impartiality and freedom from political interference.…”
Section: The Logic Of Embsmentioning
confidence: 99%